Factorize: x 2 − 6 x − 1 1 2 Note : This problem is from Aisha Maryam
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Superb solution
This was the solution i was expecting
x 2 − 6 x − 1 1 2 = x 2 − 1 4 x + 8 x − 1 1 2 = x ( x − 1 4 ) + 8 ( x − 1 4 ) = ( x − 1 4 ) ( x + 8 ) .
Superb solution sir
Problem Loading...
Note Loading...
Set Loading...
Using Prof Po-Shen Loh's different way to solve quadratic equation (video) .
Let the roots of x 2 − 6 x − 1 1 2 = 0 be 2 6 − u and 2 6 + u . Then by Vieta's formula, the sum of the two roots r + s = 3 − u + 3 + u = 6 and the product of the two roots:
( 3 − u ) ( 3 + u ) ( u − 3 ) ( u + 3 ) u 2 − 9 u 2 ⟹ u = − 1 1 2 = 1 1 2 = 1 1 2 = 1 2 1 = ± 1 1
Implying the two roots are − 8 and 1 4 and the factors are ( x − 1 4 ) ( x + 8 ) .